Artificial Intelligence in Education: Ethical Considerations in Learning Systems (Journal of responsible AI & ethics, 2026)
The integration of artificial intelligence (AI) into education has the potential to revolutionize teaching and learning systems. AI-powered educational tools are increasingly being used to deliver personalized learning experiences, automate administrative tasks, and enhance the overall learning process. However, as AI becomes more embedded in education, it raises significant ethical considerations related to fairness, privacy, accountability, and transparency. This paper explores the ethical challenges posed by AI in education, focusing on the responsible deployment of AI systems, data privacy concerns, bias in machine learning models, and the impact on educators and students. The paper also examines the role of educators, policymakers, and technologists in ensuring that AI in education is used ethically and responsibly. Through empirical data, case studies, and theoretical analysis, the paper offers insights into the potential ethical risks of AI-based learning systems and proposes strategies for mitigating these risks to ensure equitable and transparent use of AI in education. The findings emphasize the importance of integrating ethical principles such as fairness, accountability, and transparency into the design and implementation of AI systems in educational contexts.